Financial Nexus: Empirical Analysis of Knowledge, Income, and Behavior: Nexus Keuangan: Analisis Empiris tentang Pengetahuan, Pendapatan, dan Perilaku Keuangan - Tibrani, Tibrani; Wulandari, Sri; Ukhriyawati, Catur Fatchu; Wibowo, Edwin Agung; Arnesih, Arnesih (Indonesian Journal of Law and Economics Review, 2023)
This study investigates the relationship between financial knowledge, financial experience, income, lifestyle, and the financial behavior of employees in a financial institution. A sample of 37 employees from PT. Pegadaian CP Mega Legenda Batam was utilized. The research employed a saturated sample method, and validity and reliability tests were conducted for instrument trials. The findings indicate that financial knowledge exerts a positive and significant influence on financial behavior, while financial experience, income, and lifestyle do not individually impact financial behavior significantly. Moreover, when considered collectively, financial knowledge, financial experience, income, and lifestyle collectively exhibit a positive impact on financial behavior. These variables collectively account for 41.8% of the variance in financial behavior, with the remaining 58.2% attributed to unexamined factors. This study provides insights into the complex relationship between employee characteristics and financial behavior, highlighting the need for targeted interventions to enhance financial literacy and decision-making among employees, thereby fostering improved financial well-being. Highlights: Financial knowledge positively influences employee financial behavior. Financial experience, income, and lifestyle do not significantly affect financial behavior individually. Collectively, financial knowledge, experience, income, and lifestyle have a positive impact on financial behavior. Keywords: Financial Knowledge, Financial Experience, Income, Lifestyle, Financial Behavior.